2006
DOI: 10.3390/s6040350
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterisation of GaAs Gunn Diode Chips for Applications at 77 GHz in Automotive Industry

Abstract: GaAs-based Gunn diodes with graded AlGaAs hot electron injectorheterostructures have been developed under the special needs in automotive applications.The fabrication of the Gunn diode chips was based on total substrate removal andprocessing of integrated Au heat sinks. Especially, the thermal and RF behavior of thediodes have been analyzed by DC, impedance and S-parameter measurements. Theelectrical investigations have revealed the functionality of the hot electron injector. Anoptimized layer structure could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…It is observed that the I-V curves flatten for voltages above a value of around ~3 V in both cases. This behaviour is normally attributed to the occurrence of a significant intervalley scattering in the device channel [6,7,9]. It is also observed that the current is somewhat higher (~15-25%) in the device with all-ohmic contacts, in both the linear and the saturation regimes.…”
Section: Monte Carlo Simulationsmentioning
confidence: 90%
See 1 more Smart Citation
“…It is observed that the I-V curves flatten for voltages above a value of around ~3 V in both cases. This behaviour is normally attributed to the occurrence of a significant intervalley scattering in the device channel [6,7,9]. It is also observed that the current is somewhat higher (~15-25%) in the device with all-ohmic contacts, in both the linear and the saturation regimes.…”
Section: Monte Carlo Simulationsmentioning
confidence: 90%
“…Gunn diodes can generate continuous wave signal with low phase noise in the GHz range, with output powers up to 100 mW [5,6,7]. Thus, they are good candidates for mm-wave and THz emission, provided their operation frequency can be extended into the THz regime.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters I th , E th , and (nl d ) are the threshold current, threshold field and the doping density/active device length-product given by the manufacturer [13]- [15]. The last parameter, µ is the Sensitivity analysis shows that the output power changes only slightly if different estimates for the Gunn device impedance are used and that this simulation approach can be used even without exact estimates for the Gunn device impedance.…”
Section: B Output Powermentioning
confidence: 99%
“…First, the I-V characteristic in the region before the threshold voltage is very sensitive to self-heating of the active area (i.e., it depends on the test pulse duration). In [2], the results of measurements of I-V characteristics at pulse durations from 100 ns are presented. According to our estimates ( Fig.…”
Section: Introductionmentioning
confidence: 99%